Assessing public health messaging about cannabis edibles: perspectives from canadian young adults. (3rd September 2022) - Ventresca, Matt; Truman, Emily; Elliott, Charlene
Abstract: In light of the recent legalization of cannabis in Canada, and the prevalence of edibles as a preferred mode of consumption for young adults, there is a need for evidence-based youth-targeted public health messaging on edibles that resonates with this audience. To explore Canadian young adult views on existing public health messaging regarding cannabis edibles, we conducted 8 focus groups with 57 university students ages 18 to 24 (32 women; 25 men). A descriptive qualitative approach was used, informed by the importance of process evaluation. Five main themes/concepts emerged from the focus group discussions. These related to: (1) message tone; (2) type and quality of information; (3) message format and venue; (4) relatability; and (5) spokespeople. Results also revealed that gender influences both reception to spokespeople and the quantity of information desired in educational campaigns. Findings informed five recommendations for future Canadian public health campaigns, including avoiding negative or moralizing messages; providing specific information about edibles and their effects; creating short messages for social media; being cautious when striving to create "relatable" campaigns; and finding spokespeople based on authenticity and expertise. Our findings reinforce the importance of youth input in the creation of such campaigns and suggest that young people are receptive to educational messages aligned with harm reduction principles.